"Awareness is the first step": An interprofessional course on mindfulness & mindful-movement for healthcare professionals and students. (November 2016) - Kinser, Patricia; Braun, Sarah; Deeb, George; Carrico, Caroline; Dow, Alan
Abstract: High levels of stress and related burnout in healthcare professionals (HCPs) are prevalent and costly conditions. Mindfulness training has received recent attention as a possible prevention/intervention strategy to enhance resilience to stress and reduce risk of burnout in HCPs. The purpose of this mixed-methods pilot study was to evaluate the preliminary feasibility, acceptability, and preliminary effects of an 8-week mindfulness curriculum for interprofessional HCPs and trainees (n = 27). Qualitative findings supported feasibility and acceptability of the course for a wide variety of HCP disciplines, including nursing, dentistry, medicine, pharmacy, social work, mental health, and clinical research. Despite being limited by a small sample size, there were statistically significant reductions in perceived stress, anxiety, and specific aspects of burnout from pre-to post-intervention and there was a trend in an enhanced sense of personal accomplishment over time. Highlights: Mindfulness training is feasible to enhance resilience in healthcare professionals. Stress, anxiety, and burnout were significantly reduced after mindfulness training. Further large-scale controlled research is warranted.